2014
DOI: 10.1177/0192623314530195
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Steatosis and Necrosis in Atria and Ventricles of Rats Given Pyruvate Dehydrogenase Kinase Inhibitors

Abstract: Pharmaceutical therapies for non-insulin-dependent diabetes mellitus (NIDDM) include plasma glucose lowering by enhancing glucose utilization. The mitochondrial pyruvate dehydrogenase (PDH) complex is important in controlling the balance between glucose and fatty acid substrate oxidation. Administration of pyruvate dehydrogenase kinase inhibitors (PDHKIs) to rats effectively lowers plasma glucose but results in myocardial steatosis that in some instances is associated primarily with atrial and to a lesser degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…However, the potency of DCA is low and clinical translation is unlikely because DCA causes a peripheral neuropathy (16) along with carcinogenic effects (17). Treatment with another class of PDK inhibitors, AZD7545 (18), in normal rats caused cardiac steatosis and myocardial degeneration (19). The pathogenic effects of AZD7545 may be because of activation of PDK4 (13,20).…”
Section: The Pyruvate Dehydrogenase Complex (Pdc) Is a Key Control Pomentioning
confidence: 99%
“…However, the potency of DCA is low and clinical translation is unlikely because DCA causes a peripheral neuropathy (16) along with carcinogenic effects (17). Treatment with another class of PDK inhibitors, AZD7545 (18), in normal rats caused cardiac steatosis and myocardial degeneration (19). The pathogenic effects of AZD7545 may be because of activation of PDK4 (13,20).…”
Section: The Pyruvate Dehydrogenase Complex (Pdc) Is a Key Control Pomentioning
confidence: 99%
“…However, although small molecule PDK inhibitors can increase the recovery rate of cardiac function following simulated myocardial infarction in vitro , 61,62 these PDK inhibitors cause myocardial steatosis and sometimes death within a few days of treatment in vivo . 63 In contrast, ψPDK1 peptide selectively inhibited only excessive activation of PDK by δPKC, but not basal PDK activity. Therefore, ψPDK1 peptide will likely have a therapeutic advantage over other inhibitors of PDK activity.…”
Section: Resultsmentioning
confidence: 95%
“…4 Animal models have shown that cardiac-restricted long-chain acyl CoA synthase overexpression, administration of pyruvate kinase inhibitors, and inactivation of pituitary adenylate cyclase-activating polypeptide can all disrupt mitochondrial fatty acid metabolism and lead to lipid vacuolization in multiple tissues, including the heart, liver, and skeletal muscle. [5][6][7] Microvesicular fat accumulation in multiple organs is a hallmark of Reye syndrome. [8][9][10] This disorder is characterized by rapidly progressive encephalopathy, usually occurring after recovery from a viral illness, such as influenza and varicella, and is strongly associated with salicylate use.…”
Section: Discussionmentioning
confidence: 99%